Silver nanowire composite citric acid cross-linked chitosan transparent conductive film and preparation method thereof
By combining silver nanowires with citric acid-crosslinked chitosan transparent conductive film, the high cost, poor flexibility and environmental protection problems of ITO are solved, and a high-performance, environmentally friendly transparent conductive film is achieved, which is suitable for flexible electronic devices.
Patent Information
- Application Number
- CN202511076566.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-01
- Publication Date
- 2025-09-09
- Estimated Expiration
- 2045-08-01
AI Technical Summary
Existing transparent conductive film materials such as ITO are costly, have poor flexibility and are biotoxic. Traditional cross-linking agents such as glutaraldehyde are not environmentally friendly. Chitosan has poor thermal stability and is too hydrophilic, which limits its application in flexible electronic devices.
Silver nanowires are composited with citric acid cross-linked chitosan transparent conductive film, citric acid is used as a cross-linking agent to improve the performance of chitosan, combined with a grid structure of silver nanowires/PET conductive film, and an environmentally friendly preparation method is used.
A transparent conductive film with excellent heat resistance, light transmittance, conductivity, flexibility and biocompatibility is prepared. It is environmentally friendly and has no toxic by-raw materials, meeting the needs of sustainable development.
Smart Images

Figure CN120613193A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of photoelectric materials, and particularly relates to a silver nanowire composite citric acid cross-linked chitosan transparent conductive film and a preparation method thereof. Background Art
[0002] With the rapid development of information technology, the application of flexible transparent electrodes in optoelectronic devices is expanding due to their superior mechanical properties, such as bendability and foldability, as well as their excellent light transmittance and electrical conductivity. Indium tin oxide (ITO), a traditional transparent conductive film material, is widely used in optoelectronic devices due to its high transparency, excellent conductivity, good chemical stability, and high heat resistance. However, the scarcity of indium resources leads to high production costs for ITO. Furthermore, ITO's lack of flexibility, susceptibility to cracking during application, and biotoxicity limit its application in flexible electronic devices. Therefore, the development of low-cost, environmentally friendly flexible transparent films has become a research focus.
[0003] Silver nanowires (AgNWs) are simple to prepare, possess a certain degree of flexibility, and offer optoelectronic properties comparable to those of indium tin oxide (ITO). Conductive films can be fabricated in a variety of ways at a fraction of the cost, making AgNW transparent conductive films a promising alternative to ITO. Scientists have explored using polyimide (PI), polydimethylsiloxane (PDMS), and polyethylene terephthalate (PET) as substrates for AgNW composite transparent conductive films. However, these substrates are difficult to degrade, placing a significant environmental burden. Biodegradable substrates such as cellulose, gelatin, starch, polylactic acid, polyvinyl alcohol, and chitosan can be used as substrates for transparent electrodes, reducing environmental pollution and addressing sustainable development needs. Chitosan, with its excellent film-forming properties, biocompatibility, and biodegradability, is an environmentally friendly material with significant potential. However, its poor thermal stability and hydrophilic nature limit its applications. In recent years, efforts have been made to improve its properties through crosslinking or the addition of fillers. Glutaraldehyde is currently the most commonly used crosslinking agent, but its biotoxicity poses a significant environmental risk. Summary of the Invention
[0004] In response to the shortcomings of existing methods, the present invention provides a silver nanowire composite citric acid cross-linked chitosan transparent conductive film and a preparation method thereof. The silver nanowires on the conductive film have a grid structure, and citric acid cross-linked chitosan is used as the substrate of the conductive film. The obtained conductive film has excellent heat resistance, light transmittance and conductivity. Moreover, the preparation method is simple and easy, uses no toxic by-raw materials, and is safe and environmentally friendly.
[0005] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a silver nanowire composite citric acid cross-linked chitosan transparent conductive film comprises the following steps: (1) Chitosan, citric acid, and deionized water were added to a beaker in sequence and stirred evenly. Acetic acid and glycerol were then added in sequence, and the mixture was stirred continuously. The mixture was then placed under high temperature to react and obtain a citric acid cross-linked chitosan solution. (2) Cleaning and drying the PET, and then spraying the silver nanowire suspension evenly on the PET surface to obtain a silver nanowire / PET conductive film; (3) coating the citric acid cross-linked chitosan solution described in step (1) on the surface of the silver nanowire / PET conductive film described in step (2), drying it, and then peeling the film from the PET to obtain the product.
[0006] Preferably, the usage ratio of chitosan, citric acid, acetic acid, glycerol and deionized water in step (1) is: 2-3 g: 1.6-2.4 g: 1.3-2 g: 0.5-0.75 g: 100 mL.
[0007] Preferably, the high temperature in step (1) is 120-140° C., and the reaction time is 15-20 min.
[0008] Preferably, the spraying conditions in step (2) are: carrier gas pressure of 100-150 kPa, spraying speed of 14-18 μL / s, and spraying distance of 5-8 cm.
[0009] Preferably, the silver nanowire suspension in step (2) is a silver nanowire ethanol suspension with a concentration of 0.5-1.0 mg / mL.
[0010] Preferably, the silver nanowires in the silver nanowire suspension in step (2) have a length of 20-30 μm and a diameter of 20-40 nm.
[0011] Preferably, the coating method of the citric acid cross-linked chitosan solution in step (3) is spin coating, coating or casting.
[0012] A silver nanowire composite citric acid cross-linked chitosan transparent conductive film prepared by the preparation method.
[0013] The positive beneficial effects of the present invention are: 1. The present invention uses natural and non-toxic citric acid as a cross-linking agent. Citric acid is added during the preparation of chitosan solution. The carboxyl groups in the citric acid combine with the amino groups of chitosan to form an ester structure, which improves the water absorption of chitosan and increases the mechanical strength and heat resistance of the chitosan film.
[0014] 2. The present invention prepares a silver nanowire / PET conductive film with a grid structure on a PET surface by controlling the carrier gas pressure, spraying speed, and spraying distance, thereby improving the optoelectronic performance. Citric acid-crosslinked chitosan is used as the substrate for the conductive film, thereby improving the heat resistance of the conductive film. This invention is the first to prepare a silver nanowire-composite citric acid-crosslinked chitosan transparent conductive film with excellent heat resistance, light transmittance, conductivity, flexibility, biocompatibility, and biodegradability. It is an environmentally friendly optoelectronic material. Furthermore, the preparation method is simple and easy, uses non-toxic by-raw materials, and is safe and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a SEM image of the conductive film of Example 1 of the present invention; Figure 2 TG and DTG curves of the conductive film of Example 1 of the present invention; Figure 3 TG and DTG curves of the conductive film in Comparative Example 1 of the present invention; Figure 4 This is an SEM image of the conductive film in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0016] The present invention is further described below with reference to some specific embodiments.
[0017] Example 1 A method for preparing a silver nanowire composite citric acid cross-linked chitosan transparent conductive film comprises the following steps: (1) Weigh 3 g of chitosan, 2.4 g of citric acid, and 100 mL of deionized water into a beaker, stir for 2 min, then add 2 g of acetic acid and 0.75 g of glycerol, stir vigorously at room temperature for 4 h, and then react at 130 °C for 15 min to obtain a citric acid cross-linked chitosan solution. (2) The PET was cleaned and dried, and then 1.5 mL of the silver nanowire suspension was evenly sprayed on the 5 cm × 5 cm PET surface using a spray gun. The carrier gas pressure was 150 kPa, the spraying speed was 16 μL / s, and the spraying distance was 7 cm. The film was dried to obtain a silver nanowire / PET conductive film. The solvent of the silver nanowire suspension is ethanol, and the concentration of the silver nanowire suspension is 0.5 mg / mL, wherein the silver nanowires have a length of 30 μm and a diameter of 20 nm; (3) Spin-coat the citric acid cross-linked chitosan solution described in step (1) onto the surface of the silver nanowire / PET conductive film described in step (2) at a spin-coating speed of 500 rpm for 50 s, then place the film in a drying oven at 55°C for 4 h, and finally peel the film off the PET to obtain the film.
[0018] The transmittance of the conductive film of this embodiment at 550nm is 79.6%, and the square resistance is 40.3Ω / sq; the scanning electron microscopy and thermogravimetric test results of the conductive film of this embodiment are shown in FIG. Figure 1 and Figure 2 .
[0019] Depend on Figure 1 It can be seen that the conductive film prepared in the present invention has a grid structure.
[0020] Depend on Figure 2 It can be seen that in the first stage (0-150°C), the weight loss rate of the film is only 6%, and the weight loss in this stage is mainly caused by the evaporation of residual moisture and acetic acid in the film; in the second stage (150°C-300°C), the weight loss rate of the film is 24%, and the weight loss in this stage is mainly caused by the volatilization of propylene glycol; the weight loss rate of the conductive film prepared by the present invention does not exceed 10% at 200°C, and the conductive film of the present invention has a high heat resistance temperature.
[0021] Example 2 A method for preparing a silver nanowire composite citric acid cross-linked chitosan transparent conductive film comprises the following steps: (1) Weigh 2 g of chitosan, 1.6 g of citric acid, and 100 mL of deionized water into a beaker, stir for 2 min, then add 2 g of acetic acid and 0.5 g of glycerol, stir vigorously at room temperature for 4 h, and then react at 130 °C for 15 min to obtain a citric acid cross-linked chitosan solution; (2) The PET was cleaned and dried, and then 2.5 mL of the silver nanowire suspension was evenly sprayed on the 5 cm × 5 cm PET surface using a spray gun. The carrier gas pressure was 150 kPa, the spraying speed was 16 μL / s, and the spraying distance was 7 cm. The film was dried to obtain a silver nanowire / PET conductive film. The solvent of the silver nanowire suspension is ethanol, and the concentration of the silver nanowire suspension is 0.5 mg / mL, wherein the silver nanowires have a length of 30 μm and a diameter of 20 nm; (3) Spin-coat the citric acid cross-linked chitosan solution described in step (1) onto the surface of the silver nanowire / PET conductive film described in step (2) at a spin-coating speed of 500 rpm for 50 s, then place the film in a drying oven at 55°C for 4 h, and finally peel the film off the PET to obtain the film.
[0022] The transmittance of the conductive film of this embodiment at 550 nm is 71.7%, and the sheet resistance is 23.4Ω / sq.
[0023] Example 3 A method for preparing a silver nanowire composite citric acid cross-linked chitosan transparent conductive film comprises the following steps: (1) Weigh 2.5 g chitosan, 1.6 g citric acid, and 100 mL deionized water into a beaker, stir for 2 min, then add 1.3 g acetic acid and 0.5 g glycerol, stir vigorously at room temperature for 4 h, and then react at 130 ° C for 15 min to obtain a citric acid cross-linked chitosan solution; (2) The PET was cleaned and dried, and then 4 mL of the silver nanowire suspension was evenly sprayed on the 5 cm × 5 cm PET surface using a spray gun. The carrier gas pressure was 150 kPa, the spraying speed was 16 μL / s, and the spraying distance was 7 cm. The film was dried to obtain a silver nanowire / PET conductive film. The solvent of the silver nanowire suspension is ethanol, and the concentration of the silver nanowire suspension is 0.5 mg / mL, wherein the silver nanowires have a length of 30 μm and a diameter of 20 nm; (3) Spin-coat the citric acid cross-linked chitosan solution described in step (1) onto the surface of the silver nanowire / PET conductive film described in step (2) at a spin-coating speed of 500 rpm for 50 s, then place the film in a drying oven at 55°C for 4 h, and finally peel the film off the PET to obtain the film.
[0024] The transmittance of the conductive film of this embodiment at 550 nm is 67.9%, and the sheet resistance is 7.6Ω / sq.
[0025] Comparative Example 1 A method for preparing a silver nanowire composite chitosan conductive film comprises the following steps: (1) Add 3 g of chitosan to a beaker containing 100 mL of deionized water and stir for 2 min. Then, add 2 g of acetic acid and 0.75 g of glycerol, respectively, and stir vigorously at room temperature for 4 h to obtain a chitosan solution. (2) The PET was cleaned and dried, and then 1.5 mL of the silver nanowire suspension was evenly sprayed on the 5 cm × 5 cm PET surface using a spray gun. The carrier gas pressure was 150 kPa, the spraying speed was 16 μL / s, and the spraying distance was 7 cm. The film was dried to obtain a silver nanowire / PET conductive film. The solvent of the silver nanowire suspension is ethanol, and the concentration of the silver nanowire suspension is 0.5 mg / mL, wherein the silver nanowires have a length of 30 μm and a diameter of 20 nm; (3) Spin-coat the chitosan solution described in step (1) onto the surface of the silver nanowire / PET conductive film described in step (2) at a spin-coating speed of 500 rpm for 50 s, then place the film in a drying oven at 55°C for 4 h, and finally peel the film off the PET.
[0026] The transmittance of the conductive film of this embodiment at 550nm is 80.4%, and the square resistance is 43.5Ω / sq; the thermogravimetric test results of this comparative example are shown in FIG. Figure 3 .
[0027] As shown in Figure 3, during the first stage (0-150°C), the film's weight loss was 8.9%, primarily due to the evaporation of residual moisture and acetic acid within the film. During the second stage (150-300°C), the film's weight loss was 39.6%, primarily due to the volatilization of glycerol. Compared to Example 1 of the present invention, the weight loss rates at each stage were significantly higher, indicating a decrease in heat resistance. This is primarily due to the cross-linking structure of the citric acid-cross-linked chitosan, which slows the volatilization of various components and improves the heat resistance of the conductive film.
[0028] Comparative Example 2 A method for preparing a silver nanowire composite citric acid cross-linked chitosan conductive film comprises the following steps: (1) Weigh 3 g of chitosan, 2.4 g of citric acid, and 100 ml of deionized water into a beaker and stir for 2 min. Then, add 2 g of acetic acid and 0.75 g of glycerol, stir vigorously at room temperature for 4 h, and then react at 130 °C for 15 min to obtain a citric acid cross-linked chitosan solution. (2) The glass was cleaned and dried, and then 1.5 mL of the silver nanowire suspension was evenly sprayed on a 5 cm × 5 cm glass surface using a spray gun. The carrier gas pressure was 150 kPa, the spraying speed was 16 μL / s, and the spraying distance was 7 cm. The glass was dried to obtain a silver nanowire conductive network. The silver nanowire suspension solvent is ethanol, and the concentration of the silver nanowire suspension is 0.5 mg / mL, wherein the silver nanowires have a length of 30 μm and a diameter of 20 nm; (3) Spin-coat the citric acid cross-linked chitosan solution described in step (1) onto the surface of the silver nanowire conductive network described in step (2) at a spin-coating speed of 500 rpm for 50 s, then place the solution in a drying oven at 55°C for 4 h, and finally peel the film off the glass to obtain the film.
[0029] The transmittance of the conductive film of this embodiment at 550nm is 75.2%, and the square resistance is 50.4Ω / sq; the scanning electron microscope of the conductive film of this embodiment shows Figure 4 .
[0030] Depend on Figure 4 It can be seen that when the substrate PET is replaced with glass, the silver nanowires in the conductive film do not have a network structure, the transmittance is reduced, and the conductive performance is reduced.
[0031] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention and are not limiting. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in this field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a silver nanowire composite citric acid cross-linked chitosan transparent conductive film, characterized in that: The following steps are involved: (1) Chitosan, citric acid, and deionized water were added to a beaker in sequence and stirred evenly. Acetic acid and glycerol were then added in sequence, and the mixture was stirred continuously. The mixture was then placed under high temperature to react and obtain a citric acid cross-linked chitosan solution. (2) Cleaning and drying the PET, and then spraying the silver nanowire suspension evenly on the PET surface to obtain a silver nanowire / PET conductive film; (3) coating the citric acid cross-linked chitosan solution described in step (1) on the surface of the silver nanowire / PET conductive film described in step (2), drying it, and then peeling the film off the PET to obtain the product.
2. The method for preparing the silver nanowire composite citric acid cross-linked chitosan transparent conductive film according to claim 1, characterized in that: The dosage ratio of chitosan, citric acid, acetic acid, glycerol and deionized water in step (1) is: 2-3g: 1.6-2.4g: 1.3-2g: 0.5-0.75g: 100mL.
3. The method for preparing the silver nanowire composite citric acid cross-linked chitosan transparent conductive film according to claim 1, characterized in that: The high temperature in step (1) is 120-140° C., and the reaction time is 15-20 min.
4. The method for preparing the silver nanowire composite citric acid cross-linked chitosan transparent conductive film according to claim 1, characterized in that: The spraying conditions in step (2) are: carrier gas pressure of 100-150 kPa, spraying speed of 14-18 μL / s, and spraying distance of 5-8 cm.
5. The method for preparing the silver nanowire composite citric acid cross-linked chitosan transparent conductive film according to claim 1, characterized in that: The silver nanowire suspension in step (2) is a silver nanowire ethanol suspension with a concentration of 0.5-1.0 mg / mL.
6. The method for preparing the silver nanowire composite citric acid cross-linked chitosan transparent conductive film according to claim 5, characterized in that: The silver nanowires in the silver nanowire suspension in step (2) have a length of 20-30 μm and a diameter of 20-40 nm.
7. The method for preparing the silver nanowire composite citric acid cross-linked chitosan transparent conductive film according to claim 1, characterized in that: The coating method of the citric acid cross-linked chitosan solution in step (3) is spin coating, coating or casting.
8. A silver nanowire composite citric acid cross-linked chitosan transparent conductive film prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Metal nanowire composite transparent conductive film, preparation method and application thereof
CN104934094A
Chitosan flexible transparent conductive film based on silver nanowire conductive network
CN107633919A
Chitosan transparent conductive film based on silver nanowire network and preparation method thereof
CN109524173A
Embedded high-temperature-resistant transparent conductive film as well as preparation method and application thereof
CN112053800A
Preparation method of high-performance chitosan fiber
CN112323181A